Herbal Therapies in Cancer Patients: Managing Side Effects and Improving Quality of Life - Keshav Anand; Harpreet Kaur Massaon; P. K. Prabhakar (Sumatera Medical Journal, 2024)
Background: As conventional cancer treatments often induce a myriad of adverse effects, ranging from nausea and fatigue to pain and emotional distress, the integration of herbal therapies has gained attention as a potential complementary approach. Objective: The review synthesizes existing literature, drawing upon both preclinical and clinical studies, to evaluate the efficacy and safety of various herbs in alleviating common side effects associated with cancer therapies. Methods: This review article employs a narrative review approach, systematically collecting and analyzing findings from preclinical and clinical studies. Results: Special emphasis is placed on the potential benefits of herbal interventions in addressing physical symptoms, such as nausea and pain, as well as psychological and emotional challenges faced by cancer patients. Furthermore, the review explores the mechanisms of action behind these herbal interventions and potential synergies with conventional treatments. Conclusion: By providing a critical analysis of the current state of knowledge, this review aims to guide healthcare professionals, researchers, and patients in making informed decisions regarding the integration of herbal therapies into cancer care, ultimately improving the supportive care and quality of life for individuals undergoing cancer treatment.